Tampilan Berbagai Karakter Galur-Galur Kedelai F5 Hasil Seleksi Persilangan Grobogan dan KM19 - M Syofyan Tanjung; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The objectives of this research were to look at phenotypic performance of F5 lines developed by selecting from the cross between Grobogan and Galur KM19 and to determined the potential lines for F6 generation.Thirteen genotypesconsisting of 11 F5 lines and their two parents; ie, Grobogan and KM19 were grown in The Experiment Farm of the Fakulty of Agriculture, University of Riau near Pekanbaru. Each genotype was planted in a plot of 200 cm long and 120 cm in wide with planting space of 40 cm x 20 cm by using a randomized block design with three replications.Traits observed were plant height, number of branches, date to flowering, time to harvest, number of filled pod per plant, number of seeds per plant, seeds weight per plant, 100-seed weight and seed yield m-2. Analysis of Variance followed by Dunnett”s test at p=0.05 were perform by using SAS Program version 9.0. The results suggested somesignificant differencesamong F5 lines to the parents served as a control for several traits. Significant difference included for plant height, branch numbers, date to harvest, number of filled pod per plant, seeds number per plant, seed weight per plant, andseeds yield m-2. A significant Variance and heritability were detected for number of seeds per plant, weight of seeds per plant, and seeds yield m-2 indicating that those character is controlled more by geneticsTwo high yield potensial lines included GK19-3-12 dan GK 19-3-31 were obtained due to their higher values of yield components, while other lines had relatively similar value of traits compare to their parents.Keywords: line performance, yield potential, genotypic varianceyield components.